Assessment of Financial Literacy and Investment Preference by Individual Investor’s: A Case Study of Cuttack City, Odisha - et. al., Dhananjay Banthia, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The significance of financial literacy is globally acknowledged as a key component for financial well-being of individuals as well as for financial stability of a nation.The call of present time is to empower the individual investor with basic as well as advance level of Financial Literacy (Financial Knowledge & Skills) which will help them to make wise decision while selecting the right saving/investment solutions for their financial goals. Structure questionnaires have been used to assess Basic Financial Literacy Level & Investment Preference of Individual Investor’s in Cuttack City, Odisha (Sample Size N=120). From the study it has conclude that Financial Literacy Level is influencing the investment preference of Individual investor. Individual investor should take initiative to self-educate themselves and grow their financial knowledge, As we all are living in perplexing times, the waiting game will not help them, they can take a baby step to start with understanding the basics of money management & its importance and evolving themselves into smart investor/spender. When there is change of mind set among individual investor from the need based approach to a want based, the individual feels connected to the financial world, it improves saving and investing decisions to a greater extent.